Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Climate warming could free cold‐adapted trees from C‐conservative allocation strategy of storage over growth - Quan Zhou; Hang Shi; Rui He; Haikun Liu; Wenting Zhu; Shengjun Wu; Quanfa Zhang; Haishan Dang (Global Change Biology, 2024)
Carbon allocation has been fundamental for long‐lived trees to survive cold stress at their upper elevation range limit. Although carbon allocation between non‐structural carbohydrate (NSC) storage and structural growth is well‐documented, it still remains unclear how ongoing climate warming influences these processes, particularly whether these two processes will shift in parallel or respond divergently to warming. Using a combination of an in situ downward‐transplant warming experiment and an ex situ chamber warming treatment, we investigated how subalpine fir trees at their upper elevation limit coordinated carbon allocation priority among different sinks (e.g., NSC storage and structural growth) at whole‐tree level in response to elevated temperature. We found that transplanted individuals from the upper elevation limit to lower elevations generally induced an increase in specific leaf area, but there was no detected evidence of warming effect on leaf‐level saturated photosynthetic rates. Additionally, our results challenged the expectation that climate warming will accelerate structural carbon accumulation while maintaining NSC constant. Instead, individuals favored allocating available carbon to NSC storage over structural growth after 1 year of warming, despite the amplification in total biomass encouraged by both in situ and ex situ experimental warming. Unexpectedly, continued warming drove a regime shift in carbon allocation priority, which was manifested in the increase of NSC storage in synchrony to structural growth enhancement. These findings imply that climate warming would release trees at their cold edge from C‐conservative allocation strategy of storage over structural growth. Thus, understanding the strategical regulation of the carbon allocation priority and the distinctive function of carbon sink components is of great implication for predicting tree fate in the future climate warming.

Asymmetric effects of daytime and nighttime warming on alpine treeline recruitment - Hang Shi; Quan Zhou; Rui He; Quanfa Zhang; Haishan Dang (Global Change Biology, 2023)
Trees at their upper range limits are highly sensitive to climate change, and thus alpine treelines worldwide have changed their recruitment patterns in response to climate warming. However, previous studies focused only on daily mean temperature, neglecting the asymmetric influences of daytime and nighttime warming on recruitments in alpine treelines. Here, based on the compiled dataset of tree recruitment series from 172 alpine treelines across the Northern Hemisphere, we quantified and compared the different effects of daytime and nighttime warming on treeline recruitment using four indices of temperature sensitivity, and assessed the responses of treeline recruitment to warming‐induced drought stress. Our analyses demonstrated that even in different environmental regions, both daytime and nighttime warming could significantly promote treeline recruitment, and however, treeline recruitment was much more sensitive to nighttime warming than to daytime warming, which could be attributable to the presence of drought stress. The increasing drought stress primarily driven by daytime warming rather than by nighttime warming would likely constrain the responses of treeline recruitment to daytime warming. Our findings provided compelling evidence that nighttime warming rather than daytime warming could play a primary role in promoting the recruitment in alpine treelines, which was related to the daytime warming‐induced drought stress. Thus, daytime and nighttime warming should be considered separately to improve future projections of global change impacts across alpine ecosystems.

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

T4 ‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea - Huifang Li; Lu Liu; Yu Wang; Lanlan Cai; Maoqiu He; Long Wang; Chen Hu; Nianzhi Jiao; Rui Zhang (Environmental Microbiology, 2021)
Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operational taxonomic units were affiliated with previously defined Marine, Estuary, Lake and Paddy Groups. A clear viral biogeographic pattern was observed along the environmental gradient from the estuary to open sea. Marine Groups I and IV had a wide geographical distribution, whereas Marine Groups II, III and V were abundant in lower‐salinity continental or eutrophic environments. A significant distance‐decay pattern was noted for the T4‐like viral community, especially for those infecting cyanobacteria. Both deterministic and dispersal processes influenced viral community assembly, although environmental selection (e.g. temperature, salinity, bacterial abundance and community, etc.) had a greater impact than spatial distance. Network analysis confirmed the strong association between viral and bacterial community composition, and suggested a diverse ecological relationship (e.g. lysis, co‐infection or mutualistic) between and within viruses and their potential bacterial hosts.

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae - Shengpei Zhang; Xiu Liu; Lianwei Li; Rui Yu; Jialiang He; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2017)
Summary The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are involved in vesicle transport. Together with GTPase‐activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae , we identified MoGlo3 as an ArfGAP protein that is homologous to Glo3p of the budding yeast Saccharomyces cerevisiae . As suspected, MoGlo3 partially complements the function of yeast Glo3p. Consistent with findings in S. cerevisiae , MoGlo3 is localized to the Golgi, and that the localization is dependent on the conserved BoCCS domain. We found that MoGlo3 is highly expressed during conidiation and early infection stages and is required for vegetative growth, conidial production and sexual development. We further found that the Δ Moglo3 mutant is defective in endocytosis, scavenging of the reactive oxygen species, and in the response to endoplasmic reticulum (ER) stress. The combined effects result in failed appressorium function and decreased pathogenicity. Moreover, we provided evidence showing that the domains including the GAP, BoCCS and GRM are all important for normal MoGlo3 functions. Our studies further illustrate the importance of normal membrane trafficking in the physiology and pathogenicity of the rice blast fungus.

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .